The opinions and experiences of primary school teachers with the implementation of the Shoah theme into teaching - Milan Mašát (Discover Education)
Abstract The main goal of the contribution is the presentation of selected results of a quantitative research investigation, the core of which was to find out the experiences and opinions of teachers working professionally at the first level of primary schools on the implementation of the Shoah (Holocaust) theme into teaching at the relevant level of institutional education. A total of 84 respondents filled out the questionnaire, 78 women and 6 men. The motivation for the implementation of this research investigation was to determine the current situation in the field of integrating the events of the Shoah (Holocaust) into real teaching at the first level of primary schools, because we are convinced that the defined events of this historical phase are suitable for presentation at this level of education. In this article, we discuss the pedagogical methods and approaches that the defined sample of respondents consider adequate in relation to the presentation of this line of events of the Second World War to pupils of the first level of primary school. Based on the results, it can be concluded that the respondents are aware of the necessity to include the defined line of events of the Second World War in teaching at the first level of primary schools, and this when using adequate methods and forms of teaching. Working with authentic images appears to them to be the most suitable, while teachers with experience of up to ten years (including) would like to use them especially to familiarize pupils with a given historical stage (knowledge of history), pedagogues with longer experience consider it important to use the legacy of the Holocaust to develop positive axiological values of pupils.